Sinkronisasi Prinsip Good Environmental Governance dalam Kebijakan Green Building: Studi Perbandingan Jakarta dan Surabaya - Syaharani, Zevanya Praja (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Water resource management in Indonesia faces complex challenges due to policy discrepancies between central and regional governments. These inconsistencies often result in overlapping authority, inefficient policy implementation, and weak coordination in inter-regional river basin management. Using a normative juridical approach with analysis of relevant laws and regulations, this study aims to identify the causes of policy disharmony and provide recommendations to strengthen policy harmonization across regions in water resource management. The findings indicate that harmonization is essential to ensure sustainability, interregional equity, and policy effectiveness. Strengthening the central government’s coordinating role and establishing interregional coordination mechanisms are strategic steps to achieve integrated and equitable water resource governance.